Circulating microRNA-125b Levels Are Associated With the Risk of Vascular Calcification in Healthy Community-Dwelling Older Adults - Chao, Chia-Ter; Han, Der-Sheng; Huang, Jenq-Wen (Frontiers in Cardiovascular Medicine, 2021)
Background: Vascular calcification (VC) is a subclinical manifestation of vascular disease burden among older adults, conferring an elevated mortality risk. Biomarkers capable of detecting and risk-stratifying VC associated with advanced age remains unavailable, impeding our effort to provide optimal care to geriatric patients. Objectives: In this study, we aimed to investigate whether circulating miR-125b served as a potential indicator for VC in relatively healthy older adults. Methods: Community-dwelling older adults (age ≥ 65) were prospectively recruited during 2017, followed by clinical features documentation and VC rating based on aortic arch calcification (AAC) and abdominal aortic calcification (AbAC). Multiple logistic regression was done to evaluate the relationship between circulating miR-125b levels, VC presence and severity, followed by selecting the optimal cutoff point for VC diagnosis. Results: A total of 343 relatively healthy older adults (median age, 73.8 years; 40% male; 59.8% having AAC) were enrolled, with a median circulating miR-125b level of 0.012 (interquartile range, 0.003 - 0.037). Those with more severe AAC had progressively decreasing miR-125b levels (p < 0.001). Multiple regression analyses showed that having higher miR-125b levels based on the median value were associated with a substantially lower risk of AAC (odds ratio [OR] 0.022, 95% confidence interval [CI] 0.011 – 0.044) compared to those having lower ones. An optimal cutoff of miR-125b for identifying AAC was 0.008, with a sensitivity and specificity of 0.86 and 0.80, respectively. Similar findings were obtained when using AbAC as the endpoint. Conclusions: We found that miR-125b serves as an independent indicator for VC in relatively healthy older adults, and may potentially be linked with VC pathophysiology.